Exercise-induced bronchoconstriction and non-specific airway hyperreactivity in patients suffering from bronchial asthma - Novković Dobrivoje; Škuletić Vesna; Vulin Aleksandra; Cvetković Gordana (Vojnosanitetski Pregled)
Background/Aim. Physical activity is a common stimulus of asthmatic symptoms manifestation. Airway hyperreactivity is a predisposing cause of exercise induced bronchial obstruction, diagnosed by histamine inhalation. The aim of this study was to determine the relation between the amounts of histamine needed to induce non-specific airway hyperreactivity and exercise-induced bronchial obstruction. Methods. This randomized cross-over study included 160 male patients (age 19-27 years) suffering from bronchial asthma who showed positive results as the reaction after the histamine bronchial provocation test. Histamine concentrations were in a range of 0.03 to 4 mg/mL. Each patient participated in the exercise stress test conducted on a conveyor belt. The results of the exercise stress test were considered positive if the FEV1 level dropped by at least 15% from its initial value, 5-10 minutes after the test. Results. All the patients showed positive results as the reaction after the histamine bronchial provocation test, while 50 of them showed positive results after the exercise-induced stress test. There was a statistically highly significant difference in administrated histamine concentrations between the group of patients that had positive results on exercise stress test and those who did not (1mg/mL vs 0.5mg/mL; U = 1678; p < 0.01). Also, there was a statistically significant difference concerning the frequency of the positive results regarding histamine concentration after induced stress test (χ2 = 10.885; p = 0.001). Among the patients with positive results, there was a statistically highly significant number of patients with bronchial obstruction induced by less than 2 mg/mL of histamine (p < 0.01). A statistically significant relation between the amount of histamine needed to induce bronchial obstruction and the results of the exercise stress test (p < 0.01) was also observed after the testing. Conclusion. In the group of patients with positive results after the exercise-induced stress test, there were significantly more patients with positive results to non-specific bronchial provocation test with lower histamine concentrations. Histamine concentrations needed to induce non-specific hyperreactivity of asthmatic airway were shown to be related to the reactivity to physical effort.